Remarkably High Conversion Efficiency of Inverted Bulk Heterojunction Solar Cells: From Ultrafast Laser Spectroscopy and Electron Microscopy to Device Fabrication and Optimization. Issue 11 (5th April 2016) - Alsulami, Qana A.; Murali, Banavoth; Alsinan, Yara; Parida, Manas R.; Aly, Shawkat M.; Mohammed, Omar F.
Abstract : In organic donor–acceptor systems, ultrafast interfacial charge transfer (CT), charge separation (CS), and charge recombination (CR) are key determinants of the overall performance of photovoltaic devices. However, a profound understanding of these photophysical processes at device interfaces remains superficial, creating a major bottleneck that circumvents advancements and the optimization of these solar cells. Here, results from time‐resolved laser spectroscopy and high‐resolution electron microscopy are examined to provide the fundamental information necessary to fabricate and optimize organic solar cell devices. In real time, CT and CS are monitored at the interface between three fullerene acceptors (FAs) (PC71 BM, PC61 BM, and IC60 BA) and the PTB7‐Th donor polymer. Femtosecond transient absorption (fs‐TA) data demonstrates that photoinduced electron transfer from the PTB7‐Th polymer to each FA occurs on the sub‐picosecond time scale, leading to the formation of long‐lived radical ions. It is also found that the power conversion efficiency improves from 2% in IC60 BA‐based solar cells to >9% in PC71 BM‐based devices, in support of our time‐resolved results. The insights reported in this manuscript provide a clear understanding of the key variables involved at the device interface, paving the way for the exploitation of efficient CS and subsequently improving the photoconversion efficiency. Abstract : A complete understanding of the charge transfer, charge separation, and charge recombination at D/A interfaces is integral for boosting solar cell photoconversion efficiency (PCE). Time‐resolved laser spectroscopy and high‐resolution electron microscopy provide a basis for accomplishing the high performance solar cell. The device optimization enhanced the PCE from 2% in IC60 BA‐based to >9% in PC71 BM‐based solar cells.